Photosubstitution of Thiosemicarbazide to VI B and VII B Group Metal Carbonyls - Subasi, E.; Cetin, S. (Asian Journal of Chemistry, 2013)
A series of new metal carbonyl complexes of VIB and VIIB groups having the general compositions cis-[M(CO)4(h2-N,S-TSC)], [M = Cr; 1, Mo; 2, W; 3] and fac-[ReBr(CO)3(h2-N,N-TSC)], 4 and [(h5-Cp)Mn(CO)(h2-N,N-TSC)], 5 have been prepared by photochemical reactions of thiosemicarbazide (TSC) and metal carbonyls in THF. The complexes have been characterized by elemental analysis, LC-mass spectrometry, FT-IR and 1H NMR spectroscopy. The spectral data suggest the involvement of sulfur and terminal amino nitrogen of thiosemicarbazide in coordination to the central metal ion for VIB metal carbonyl complexes whereas the terminal amino nitrogen and thioamide nitrogen of thiosemicarbazide in coordination to the central metal ion for VIIB metal carbonyl complexes. On the basis of spectral studies, an octahedral geometry has been assigned for all of the complexes.